THE EFFECT OF PROFITABILITY, CAPITAL STRUCTURE AND CORPORATE VALUES ON RETURN OF SHARES (TELECOMMUNICATIONS SUB SECTOR IN INDONESIA STOCK EXCHANGE 2014-2018) - Wulandari, Asih Try; Herawati, Aty (Dinasti International Journal of Digital Business Management, 2019)
The development of increasingly stringent business world in Indonesia will create an increasingly sharp competition between companies. Firms in the industry in Indonesia is a land for investors to invest capital to be invested in various forms of securities. So it is not wrong for the company's various aspects and types become part of the capital market. This study was conducted to determine the effect of ROE, DER and PBV to Stock Return on Telecommunications Sector Sub Listed in Indonesia Stock Exchange. This study uses annual data for the observation period from 2014 until 2018. The research type is descriptive causality. The data used is the data panel that is a combination of annual time series data and cross section were processed using panel data regression analysis. The population is all Sub-Sector Telecommunications listed in Indonesia Stock Exchange from 2014 until 2018 the number of 5 companies. The sampling technique used purposive sampling, found a sample of four companies with the observation of 5 years in order to obtain total observation as much as 20. Data were obtained from the Indonesia Stock Exchange, and Yahoo Finance. Analysis of the data in this study is panel data regression. The model used is the Common Effect Model. The analysis showed that the ROE does not have a significant effect on stock returns, DER has no significant effect on stock returns, while PBV positive and significant effect Stock Return on Telecommunications Sector Sub Listed in Indonesia Stock Exchange.